Role of SR vacuum cannula as novel technique for atonic PPH management study at Pannadhay Rajkiya Mahila Chikitsalaya and RNT Medical College, Udaipur - Damor, Priyanka; Maheshwari, Sunita; Singh, Shalini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Postpartum hemorrhage is a major obstetrical emergency and one of the important but preventable causes of maternal morbidity and mortality. It is often sudden, frequently unpredictable and catastrophic. In this study SR vacuum cannula will be applied to create negative pressure inside the uterine cavity with a specially designed uterine cannula, which is a simple, safe and cost-effective technique. The aim and objective of the study was to analyse the incidence, effectiveness of suction cannula in management of atonic PPH after failure of medical management over tamponade and the maternal outcome after suction technique. Methods: This observational study was conducted in Department of Obstetrics and Gynecology, RNT Medical College and Panna Dhay Rajkiya Mahila Chikitsalaya, Udaipur, Rajasthan. Patients requiring PPH management admitted to the obstetrics ward between August 2019 – December 2020. The Uterine Vacuum Retraction System consists of SR Suction cannula to control PPH after vaginal delivery. SR suction cannula for atonic PPH at caesarean delivery and High vacuum suction machine was used. Results: In majority of the patients bleeding was stopped within three minutes. 60 women (50%) bleeding was stopped within 3 minutes, in 38 women (31.7%) bleeding was stopped between 3-4 minutes and in 22 women (18.3%) bleeding was stopped >4 minutes. In 75 (62.5%) women negative pressure was applied only once, in 20 (16.7%) was applied two times and 25 women (20.8%) negative pressure was applied three times to stop bleeding. Blood collected in bottle after SR Cannula Application ranged from 100-150 ml. Conclusions: Vacuum suction cannulas should be made part and parcel of normal delivery tray to facilitate quick application. This simple and cost-effective technique takes very little time to organize and can stop bleeding within 3 minutes in atonic PPH as shown in this study.